Focused Research on the Challenges and Productivity of Researchers in Nigerian Academic Institutions Without Funding - Igiri, Bernard E.; Okoduwa, Stanley I. R.; Akabuogu, Ebere P.; Okoduwa, Ugochi J.; Enang, Idongesit A.; Idowu, Olanipekun O.; Abdullahi, Suleiman; Onukak, Imeh E.; Onuruka, Catherine C.; Christopher, Ogechukwu P.O.; Salawu, Akinbobola O.; Chris, Aimee O.; et al. (Frontiers in Research Metrics and Analytics, 2021)
Background: The challenge of research funding constraints has brought to bear enormous pressure on researchers. Research productivity is relevant to prestige and career progression of academic staff. However, this study aimed to explore significant challenges associated with researchers’ productivity and the impact of non-funding of research in Nigerian research and tertiary institutions. Methods: This study adopted a qualitative exploratory design involving academics at various research and tertiary institutions across the six geographical regions in Nigeria. A semi-structured questionnaire was distributed electronically to all participants who consented to take part in this study. Exactly 4,159 questionnaires were administered and 2,350 were completely filled and returned. Pearson correlation matrices with logistic regression were used for data analysis and are presented in frequencies and percentages. Results: On challenges faced by respondents, 42.98% reported a lack of research funding, 17.11% mentioned brain drain challenge while 8.85% indicated a lack of motivation. Of the 23,927 publications reported, the number of those in sciences, engineering, and medical sciences averaged 9.6, 11.5, and 9.5 respectively. The average number of publications by women (10.8) was more than by men (9.7). Lecturers had the highest average research publication number (11.8) followed by researchers (10.2) and others (3.9). Men had the highest (11.9) average number of conferences compared to women (9.2). Participants in engineering had an average number of 13.8 conferences per respondents followed by those in education (11.2), sciences (11.1), and 10.9 for those in agricultural sciences. The result revealed a negative significant correlation between research publication and academic qualification at p < 0.01. Positive significant correlation was observed between research productivity and discipline at p < 0.05. Findings show that the combined influence of the independent variables on research productivity was significant using linear regression analysis. Conclusions: The failure to prioritize research has resulted in underdevelopment in Nigeria. It is therefore imperative that the federal government prioritize research and establish a functional Special Research Trust Fund to oversee research funding in Nigeria.